2018
DOI: 10.1016/j.jalz.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alzheimer's disease risk and protective factors on cognitive trajectories in subjective memory complainers: An INSIGHT‐preAD study

Abstract: Distinct classes of cognitive trajectories were associated with risk and protective factors of AD. These associations support the notion that the identified cognitive trajectories reflect different risk for AD that may be useful for selecting high-risk individuals for intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Similarly, one of these studies observed a decline in the class which started highest, while there was an increase in the class starting lowest [33]. Another study found that all classes, except for the worst class, improved in performance over time [34]. Finally, one slope-based study observed similar cognitive function between classes at baseline, but they diverged over follow-up [35].…”
Section: Number and Shape Of Trajectoriesmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, one of these studies observed a decline in the class which started highest, while there was an increase in the class starting lowest [33]. Another study found that all classes, except for the worst class, improved in performance over time [34]. Finally, one slope-based study observed similar cognitive function between classes at baseline, but they diverged over follow-up [35].…”
Section: Number and Shape Of Trajectoriesmentioning
confidence: 84%
“…The strongest evidence for this 'stable-high' class was for a measure of general cognitive function, but this was also because most studies focused on this cognitive assessment. However, the 'stable-high' class was also observed in terms of some other cognitive domains such as memory, processing speed, and executive function [23,34,43,45,[49][50][51]. Of note, these are cognitive domains that are thought to decline more rapidly than others during the 'normal' aging process [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, AD-related neuropathological markers have been observed several years before clinical manifestation of memory symptoms (Braak and Braak, 1996;Delacourte et al, 1999;Morris et al, 1996;Serrano-Pozo et al, 2011;Mosconi et al, 2007), which suggests that AD development could be predicted before clinical onset via in vivo biomarker analysis (e.g. PET and MR imaging as well as blood or cerebrospinal fluid (CSF) biomarkers) (Markesbery, 2010;Baldacci et al, 2018;Teipel et al, 2018). Magnetic resonance imaging (MRI) has garnered interest in AD diagnosis as well as prediction of MCI to AD conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that SCD is associated with an increased likelihood of AD-related biomarker abnormalities and with increased risk of future cognitive decline and developing clinical DAD [18][19][20][21][22]. A recent study found initial evidence that cholinergic BF atrophy is already detectable in cohorts with subjective cognitive complaints [23], and may be associated with both AD biomarkers and a lower cognitive performance trajectory [23,24]. Especially, SCD in combination with proven AD pathology may re ect progression from stage 1 (asymptomatic) to stage 2 (transitional cognitive impairment) of the Alzheimer's continuum (according to the recent National Institute on Aging-Alzheimer's Association [NIA-AA] Research Framework [25].…”
Section: Introductionmentioning
confidence: 99%